All in good taste - Dolce, Holly; Kaplan, Rebecca (Editor) (kate spade new york ;, 2015)
In this charming guide to entertaining, kate spade new york throws rigid rules out the door and shares unpretentious ideas for the modern-day hostess that are easy, festive, authentic, and always with an air of deliberate polish. filled with how-tos, personal essays, anecdotes, recipes, and a liberal dash of style, all in good taste will transform you into the hostess everyone wants an invitation from. The book covers the essential lost arts--how to shuck an oyster, curate a vibrant guest list, guide a dinner-table discussion--right alongside modern conundrums such as Instagram etiquette at dinner. Whether you entertain a little or a lot, or just love being the person everyone wants to sit next to at dinner, all in good taste is the modern classic you'll treasure for years. Disclaimer: The wine stain on the cover of the book is a design element and is intentional.